2009
DOI: 10.1007/s00705-009-0381-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of equine H3N8 influenza viruses from pigs in China

Abstract: During 2004-2006 swine influenza virus surveillance, two strains of H3N8 influenza viruses were isolated from pigs in central China. Sequence and phylogenetic analyses of eight gene segments revealed that the two swine isolates were of equine origin and most closely related to European equine H3N8 influenza viruses from the early 1990s. Comparison of hemagglutinin (HA) amino acid sequences showed several important substitutions. One substitution caused the loss of a potential glycosylation site, and two substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 10 publications
0
72
0
6
Order By: Relevance
“…Sequence analysis revealed that an avian-like H3N8 influenza A virus, A/harbor seal/Massachusetts/1/2011 (seal11), was the cause of the outbreak (23). Although A(H3N8), usually found in avian, canine, equine, and swine hosts (24)(25)(26)(27), had been isolated from a seal prior to this event (28), the high mortality observed increased interest from public health officials.…”
mentioning
confidence: 99%
“…Sequence analysis revealed that an avian-like H3N8 influenza A virus, A/harbor seal/Massachusetts/1/2011 (seal11), was the cause of the outbreak (23). Although A(H3N8), usually found in avian, canine, equine, and swine hosts (24)(25)(26)(27), had been isolated from a seal prior to this event (28), the high mortality observed increased interest from public health officials.…”
mentioning
confidence: 99%
“…Ο ιός H3N8 της γρίπης των ιπποειδών ανιχνεύθηκε για πρώτη φορά σε χοίρους με αναπνευστικά συμ πτώματα, το διάστημα 2004-2006 στην Κίνα (Tu et al, 2009). Σε αντίθεση, όμως, με το στέλεχος Η3Ν8 που απομονώθηκε από τους σκύλους, αυτά τα στελέχη δεν φαίνεται να προκάλεσαν άλλες επιζωοτίες και κατατάσσονται φυλογενετικά στον Ευρωπαϊκό κλάδο, ο οποίος περιλαμβάνει στελέχη που απομονώθηκαν τη δεκαετία του 1990 (Tu et al, 2009).…”
Section: μετάδοση του ιοΰ της γρίπης των υυιοειδών σε άλλα είδη ξενιστώνunclassified
“…Σε αντίθεση, όμως, με το στέλεχος Η3Ν8 που απομονώθηκε από τους σκύλους, αυτά τα στελέχη δεν φαίνεται να προκάλεσαν άλλες επιζωοτίες και κατατάσσονται φυλογενετικά στον Ευρωπαϊκό κλάδο, ο οποίος περιλαμβάνει στελέχη που απομονώθηκαν τη δεκαετία του 1990 (Tu et al, 2009). Δεδομένου ότι το 1993 είχε απομονωθεί το στέλεχος A/Eq/Gansu/ 2/94 από επιζωοτία γρίπης σε ίππους στην Κίνα, το οποίο φυλογενετικά προσομοίαζε στα στελέχη του Ευρωπαϊκού κλάδου (Guo et al, 1995), ενισχύεται η υπόθεση ότι ο ιός που απομονώθηκε στους χοίρους προήλθε από τα ιπποειδή.…”
Section: μετάδοση του ιοΰ της γρίπης των υυιοειδών σε άλλα είδη ξενιστώνunclassified
“…In recent times, H3N8 viruses are circulating in horse where as the H7N7 subtype has not been isolated from horses for over 30 years and is presumed to be out of infections cycle at present [14]. Recently, H3N8 virus jumped the species barrier to infect dogs [4,8,16] and pigs [25]. Since the first isolation of H3N8 virus (Miami/63), these viruses have diversified into various lineages viz, Predivergent, Eurasian, and American-which on the basis of HA gene analysis has further diversified into Kentucky, South America, and Florida sublineage (clade 1 & 2) [3,5,9].…”
Section: Introductionmentioning
confidence: 99%